SIMULASI DAN EKSPERIMEN KONTROL AUTOMATIC TURRET GUN - Mohamad Nasyir Tamara; Bambang Pramujati; Hendro Nurhadi; Endra Pitowarno (Politeknik Negeri Malang, 2018)
This research presented Active Force Control (AFC) as a control method which is applied to Automatic Turret gun (ATG) in ground combat vehicles This method compares the reference force conducted by actuator with actual force of the mechanical systems that arise due to disturbances. The advantage of AFC method is its ability to handle disturbances effectively without complicated mathematical calculations. The AFC method uses Crude Approximation (CA) in the internal loop controller AFC as inertia matrix estimator as an important part in the control loop. Simulation without load on the azimuth movement shows PID controller produces the best precision with MSE of 0 degrees while RACAFC and RAC method provide MSE 0.267 degrees. In simulation on the elevation movement, the RAC method showed the best results with an estimated MSE of the targets shot of 2.42 degrees, while the PID and RACAFC method are 2.5 and 2.46 degrees. When simulation is conducted with additional load RACAFC method gives the best precision with a MSE of 0.267 and 2:46 degrees, while the PID method was 4.24 and the 10.52 degrees. RAC method produces MSE of 0.7 and 2.87 degrees. With the added load the performance of PID controller decreases. In the experiment on the constructed rig, RAC and RACAFC scheme produce smoother movement trajectory and minimum oscillation compared to the PID controller. In loaded conditions these methods are able to maintain their performance. However, these three methods can still achieve a reference point with or without load in the end of travel time